CULTURAL HYBRIDITY AND IDENTITY FORMATION IN ANITA NAIR’S WORKS - S., Mahesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian English Literature is well-known for Indian Writers’ cultural thought, mythology, cultural hybridity and provoking ideas. Anita Nair is one of the prominent writers in India for expressing the social norms and value in her writings. She involves the characters in various transformations of gender, cultural hegemony and insight of human feelings. In her writings, she portrayed the South Indian social norms with livelihood characters and sensitive themes like culture, struggles of women and social norms. She has challenged the restricted social norms and complex identity prescribed by the forefathers. Her writings prioritized the complexities of cultural hybridity, human identity in social expectation. She created the characters that showed tensions, conflicts and harmony in the diverse cultural influence. Overall, Anita Nair’s works provide the chance to the readers of contemporary Indian society to know the multifaceted nature of identity and cultural norms. Overall, Anita Nair's novels offer insightful explorations of cultural hybridity, shedding light on the multifaceted nature of identity and the ever-evolving dynamics of contemporary Indian society. She has earned a global readership for her works.